Neural Bases of Cognitive Impairments in Post-Traumatic Stress Disorders: A Mini-Review of Functional Magnetic Resonance Imaging Findings - Dossi, Gabriele; Delvecchio, Giuseppe; Prunas, Cecilia; Soares, Jair C.; Brambilla, Paolo (Frontiers in Psychiatry, 2020)
Introduction Post-Traumatic Stress Disorder (PTSD) is often associated with impairments in emotional and cognitive domains. Contrarily to the emotional sphere, neural basis underpinnings to cognitive impairments are still not well known. Methods We performed a bibliographic search on PUBMED of all the studies investigating the cognitive impairments in PTSD individuals. We considered only studies that applied cognitive tasks using a functional Magnetic Resonance Imaging technique. The inclusion criteria were met by nine studies. Results Overall, PTSD individuals reported significant impairments in the dorsolateral prefrontal cortex, anterior cingulate cortex, inferior frontal gyrus, insula, inferior temporal cortex, supplement motor area, and Default Mode Network (DMN). Moreover, abnormal activity was reported in subcortical structures (e.g. hippocampus, amygdala, thalamus) and in the cerebellum. Limitations Cognitive functioning was assessed using different cognitive tasks. Potential confounding factors such as age, sex, symptoms intensity, and comorbidities might have influenced the results. Conclusion So far, the evidence reported that PTSD is characterized by cognitive impairments in several domains, such as attention, memory and autonomic arousal, which may be due to selective dysfunctions in brain regions that are part of cortical networks, the limbic system and DMN. However, further studies are needed in order to better assess the role of cognitive impairments in PTSD and to develop more targeted therapeutic approaches.